2019
DOI: 10.1371/journal.pone.0216369
|View full text |Cite
|
Sign up to set email alerts
|

Head impacts sustained by male collegiate water polo athletes

Abstract: Water polo is a contact sport that is gaining popularity in the United States and carries a risk of repeated head impacts and concussion. The frequency and magnitude of sport-related head impacts have not been described for water polo. We aimed to compare patterns of empirically measured head impact exposure of male collegiate water polo players to patterns previously reported by a survey of current and former water polo athletes. Participants wore water polo caps instrumented with head impact sensors during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…Recent survey data reveal that 36% of USA Water Polo members report sustaining at least one concussion during their playing tenure (6), a lifetime incidence that is comparable to that observed in soccer (7). However, the respondents also reported sustaining an average of two asymptomatic head impacts during a typical practice or game, a rate of exposure consistent with prospective data from in vivo monitoring over three competitive seasons (8). In some contact sports (e.g., American football, soccer, hockey) the accumulation of these impacts is believed to contribute to clinically significant neurological dysfunction years after exposure has ceased (9,10).…”
Section: Introductionsupporting
confidence: 55%
“…Recent survey data reveal that 36% of USA Water Polo members report sustaining at least one concussion during their playing tenure (6), a lifetime incidence that is comparable to that observed in soccer (7). However, the respondents also reported sustaining an average of two asymptomatic head impacts during a typical practice or game, a rate of exposure consistent with prospective data from in vivo monitoring over three competitive seasons (8). In some contact sports (e.g., American football, soccer, hockey) the accumulation of these impacts is believed to contribute to clinically significant neurological dysfunction years after exposure has ceased (9,10).…”
Section: Introductionsupporting
confidence: 55%
“…Water polo is a contact sport that has been shown to present a risk of head impact exposure 17 and concussion, 18,19 with athletes reporting impacts from both the ball and other players. 18 A study of male collegiate water polo players utilizing head impact sensors found that a single team sustained an average of 18.4 head impacts per game.…”
Section: Introductionmentioning
confidence: 99%
“…18 A study of male collegiate water polo players utilizing head impact sensors found that a single team sustained an average of 18.4 head impacts per game. 17 An evaluation of a head impact sensor that is waterproof and compatible with a water polo cap has yet to be published. This study aimed to compare the performance of a waterproof head impact sensor in a headband attachment (for use in non-helmeted land sports) to a mode of attachment suitable for water polo.…”
Section: Introductionmentioning
confidence: 99%
“…Using multiple, single observers to record head-to-ball impacts, without recording video for offline corroboration, is a limitation of the current study and prevented us from discerning impact magnitude or impact location. Our laboratory ( Cecchi et al, 2019 ) and others ( Campbell et al, 2020 ; Cortes et al, 2017 ) have demonstrated the value of using independent review of video recordings to validate head impact data, even when field-based collection is performed using wearable impact sensors. We can assume that our measure contains some degree of human error, but these inaccuracies are not likely to be systematic.…”
Section: Discussionmentioning
confidence: 98%